Mentoring Values of Tolerance for Students of Different Religions Through Interfaith Youth Gathering - Yahya MOF; Willy Ramadan; Ilham Masykuri Hamdie (Engagement: Jurnal Pengabdian Kepada Masyarakat, 2022)
Radicalism in Indonesia is increasingly showing a very worrying increase, and youth are one of the targets of the entry of this understanding. This is evident that the involvement of youth as perpetrators of radicalism and terrorism continues to show an increasing trend. However, youth, in this case students, with a different perspective, have actually become a strength asset owned by universities to fight the power of spreading these ideas. Therefore, it is necessary to provide assistance to youth so that these assets can be maximally empowered. This assistance is carried out through the Interfaith Youth Gathering program which consists of Youth Development, Youth Gathering, and Youth Media. This program was attended by 15 people consisting of different universities and youth religious organizations. This assistance used the ABCD (Asset-Based Community Development) method with two techniques.